Belalang Kembar Siam Berkepala Dua sebagai Inspirasi Desain Busana Kostum untuk Perempuan - Purnama, Cecilia Agata; Aryani, Dewi Isma; Tan, Indra Janty (JURNAL RUPA; Vol 8 No 1 (2023): Open IssueDO - 10.25124/rupa.v8i1.5851, 2023)
The extremely rare occurrence of conjoined twins in grasshoppers served as the inspiraton for the POLYCHYPERA collecton. Photographer Juan Camarillo from South America saw this two-headed grasshopper and utlized it as a photo subject for the image ttled “Two Headed Grasshopper.” By exhibitng one head’s conditon on the front-back and top-down sides of each outit, the grasshopper’s singularity serves as a source of inspiraton for the design of costume apparel. The POLYCHYPERA costume collecton is created with the contrast impact in mind. Finding a distnctve costume design development concept using an anthropomorphic approach is how the study challenge is stated. This study aims to develop a concept and product design for dramatc-styled costume garments. By experimentaton and reading, the research method employs the project-based learning approach. The fndings of this study are antcipated to serve as a guide for comparable fashion designs that can develop the innovatve creatvity of fashion industry players.